2021
DOI: 10.3346/jkms.2021.36.e164
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between Cytology and Histology in Cervical Cancer Screening: a Multicenter Retrospective Study (KGOG 1040)

Abstract: Background Cervical cancer is the fourth common cancer in women worldwide. The Papanicolau test is the primary screening procedure to detect abnormal cervical cells. Colposcopy is the main procedure for discriminating high-grade cervical lesions. The study aimed at clarifying the discrepancy between cervical cytology and colposcopic biopsy histology as well as confounding factors. Methods Eligible patients visited thirteen tertiary hospitals for colposcopic biopsy follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
9
0
2
Order By: Relevance
“…hrHPV: Several recent studies investigated the impact of hrHPV on CHC results [ 35 , 36 , 37 ]. For example, a multicentric Korean study (Ouh et al) found a higher risk for initial overcall in patients with hrHPV [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hrHPV: Several recent studies investigated the impact of hrHPV on CHC results [ 35 , 36 , 37 ]. For example, a multicentric Korean study (Ouh et al) found a higher risk for initial overcall in patients with hrHPV [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…hrHPV: Several recent studies investigated the impact of hrHPV on CHC results [ 35 , 36 , 37 ]. For example, a multicentric Korean study (Ouh et al) found a higher risk for initial overcall in patients with hrHPV [ 35 ]. By contrast, our obtained findings did not show a strong relationship between HPV status and cytologic–histologic discrepancies ( p = 0.221).…”
Section: Discussionmentioning
confidence: 99%
“…Samaha et al [ 12 ] conducted a retrospective study of Egyptian women of ages 25–65 years, where the prevalence of hrHPV in abnormal Pap smears was 48.2%. Ouh et al [ 13 ] reported HPV positivity in 79.2% of ages 19–88 years with an abnormal Pap smear. Chinese study showed that the overall HPV infection rate was 84.37% in patients with CIN 1 and CIN 2-3 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Преимущества данной методики в простоте получения материала с возможностью самозабора и высокой чувствительности метода. Однако по сравнению с цитологическим исследованием метод имеет более низкую специфичность и высокую себестоимость [3,4]. Согласно приказу Минздрава России от 13.03.2019 № 124н «Об утверждении порядка проведения профилактического медицинского осмотра и диспансеризации определенных групп взрослого населения» на территории страны действует программа скрининга рака шейки матки, реализуемая посредством цитологического исследования.…”
Section: Introductionunclassified
“…Согласно приказу Минздрава России от 13.03.2019 № 124н «Об утверждении порядка проведения профилактического медицинского осмотра и диспансеризации определенных групп взрослого населения» на территории страны действует программа скрининга рака шейки матки, реализуемая посредством цитологического исследования. Данный тест является недорогим, высокоспецифичным, но в то же время сильно зависит от уровня подготовки персонала и правильности проведения преаналитического этапа [3][4][5].…”
Section: Introductionunclassified